BIODEGRADATION OF CHRYSENE BY CONSORTIUM OF BACILLUS CEREUS AND PSEUDOMONAS PUTIDA IN PETROLEUM CONTAMINATED-SOIL ON SLURRY-PHASE BIOREACTOR - Tuhuloula, Abubakar; Altway, Ali; Juliastuti, Sri Rachmania; Suprapto, Suprapto (Jurnal Bahan Alam Terbarukan, 2017)
Pollution by chrysene compounds in the polluted soil of petroleum, due to exploration activities, production and disposal of petroleum waste into the environment causing serious damage to the ecosystem environment, became the target of processing with bacteria as a model of remediation of pollution sites. Thus, the study focused on the use of a bacterial consortium to degrade chrysene in petroleum-contaminated soil. The study was conducted by mixing 20:80 (% wt) of contaminated soil with water. The consortium of Bacillus cereus and Pseudomonas putida 10%(v/v) and 15%(v/v) bacteria with ratios; 2:3; 1:1; 3:2 is inserted into the slurry bioreactor. Biodegradation process is run with agitation of 100 rpm and temperature 26oC – 30oC and in aeration. Identification of chrysene using gas chromatography–mass spectrometry (GCMS) and bacterial populations with haemycitometer. The initial concentration of chrysene is 24.48 ng/μL. After 49 days remediation period for a 10% (v/v) reduced chrysene bacteria consortium and bacterial populations were 8.68 ng/μL; 7.56 ng/μL; and 8.07 ng/μL; with biodegradation rate is 67.01%; 69.10%; And 64.54%. As for the 15% (v/v) bacteria consortium with the same ratio, chrysene was degraded to 2.60 ng/μL; 1.57 ng/μL; and 2.02 ng/μL and the measured chrysene biodegradation rate was 89.39%; 93.58%; And 91.73%. These findings suggest that the percentage of low crude oil is degraded because of the increasing concentration of crude oil.